DENSITY OF STATES OF N-SI⟨NI⟩ AND N-SI⟨CO⟩ UNDER PRESSURE VARIATIONS APPLIED TO THE SAMPLE - Raxmanov M. A.; Tursunov I. G. (Modern American Journals, 2025)
This study examines the influence of uniform hydrostatic pressure (UHP) on the relative resistivity ρ/ρ₀(P) of n-Si⟨Ni⟩ and n-Si⟨Co⟩ single-crystal samples and, on this basis, analyzes how the semiconductor density of states g(E,P) depends on the pressure- (deformation-) related energy. As pressure increases, the step-by-step disintegration of neutral nickel and cobalt impurity clusters results in a pronounced rise in the number of deep localized levels Nₜ(P) within the band gap, a reduction in the free-electron concentration n(P), and a two-stage increase in ρ/ρ₀(P). Using the experimental observations, qualitative links among the deformation energy E_def(P), the localized-state density Nₜ(P), and the resistivity ρ(P) are discussed, and representative plots of ρ/ρ₀(P), Nₜ(P), and g(E,P) are presented for three characteristic pressure regimes.
Keywords: hydrostatic pressure; pressure energy; semiconductor; density of states; impurity cluster; localized levels; nickel; cobalt.